Clinical and laboratory assessment of the effeciency of using a new hygienic action in the treatment of chronic generalized parodontitis in patients with hypercydin gastritis - O. L. Zolotukhina; S. A. Schnaider; L. S. Kravchenko (Kazimierz Wielki University, 2018)
At present, diseases of mucous membrane of the oral cavity (MMOC), periodontal disease remain an unresolved problem of dentistry, due to the multifactorial nature of their occurrence. The aim of the work is to increase the effectiveness of treatment of periodontal diseases, the mucous membrane of the oral cavity against a background of gastritis with an increased acid-forming function by applying pathogenetically grounded local therapy. Local application of a new apigel based on propolis and biologically active substances in the complex treatment of patients with chronic generalized periodontitis of the first degree against a background of hyperacid gastritis has a beneficial effect on the clinical symptoms of inflammation of the oral mucosa and periodontium. In comparison with patients in whom anti-inflammatory local therapy was performed using the traditional method with local use of dental gel based on chamomile flowers, patients whose treatment regimen included local apigel use noted improvement in oral dental status 5-7 days faster. The proposed method quickly removed inflammation, bleeding gums that correlated with the improvement of the hygienic state of the oral cavity. The results of the clinical and laboratory evaluation of the effectiveness of the use of the newly developed anti-inflammatory hygienic remedy for the treatment of periodontal disease in the context of heli bacterium in patients with hyperacid gastritis revealed a rapid normalization of indices of nonspecific and specific protection in the oral liquid than with conventional therapy. Under the influence of the developed local method of treatment for inflammatory diseases of MMOC and periodontal disease in patients with hyperacid gastritis, in particular, in tobacco-producing, optimal conditions are created for the elimination of violations of the immunological status of the oral cavity and the restoration of the structural and functional state of the periodontal and mucous membranes. The authors came to the conclusion that the local application of the proposed treatment method reduces the period of restoration of the structural and functional integrity of MMOC, improves the hygienic state of the cavity, promotes the rapid normalization of indices of nonspecific and specific protection in the oral fluid, preventing the development of inflammatory complications in tobacco-dependent, which increases the effectiveness of treatment and quality. the life of patients with conjunctival diseases of the digestive canal with an increased acid-forming function.